Study of ground source heat pump as cooling system for local applications - Nurul Hidayah, Abdul Samat (2010)
This report describes in detail includes a brief description of the Ground Source Heat Pump as cooling system, concentrating on hole depth and coils length. Besides, the descriptive drawings make this report very easy to understand. The main objective of this report is to determine the suitable hole depth and coils length during Ground Source Heat Pump installation. The hole depth and coils length are determined according to the different type of soil moisture. Every type of soil moisture will give different hole depth and coils length. The parameter of hole depth and coils length are determined through the equation in chapter 3. In chapter 4, there are the result of hole depth and coils length parameter that can be used according to the flow rate of R-134 A and soil moisture. Higher soil moisture will decreasing hole depth and coils length. In addition to these, this report also contains the details regarding the different type of other Ground Source Heat Pump which are used these days. Above all, this report gives a detailed description of closed looped Ground Source Heat Pump. This report will be help for those who wish to understand about the basic working of different Ground Source Heat Pump especially those who wish to study Ground Source Heat Pump as cooling system.